Genetic polymorphism of 24 Y-STR loci in Altay Hui and Kazakh populations from northwest China. (November 2020) - Li, XueBo; Zhang, Jiashuo; Li, Liangliang; Zha, Lagabaiyila; Shi, Meisen; Ding, Mingxia
Highlights: The distribution of 24 Y-STR loci in the Altay Hui and Kazakh populations were analyzed. The observed haplotype diversity and discrimination capacity were calculated. Pairwise Rst values were evaluated in AMOVA analysis and visualized using an MDS plot and a neighbor-joining tree. Altay Kazakh population keeps a distantly genetic relationship with Xishuangbanna Dai. Abstract: 24 Y-STR loci were analyzed in 223 Altay Hui individuals and 209 Altay Kazakh individuals. Haplotype diversity (HD) and discrimination capacity (DC) values were calculated. Population pairwise genetic distances ( Rst ) were evaluated in AMOVA analysis and compared between two studied populations and other populations. The relationships between populations were visualized through multidimensional scaling (MDS) and neighbor-joining (NJ) tree. The results indicated higher discrimination power in the Altay Kazakh and Hui populations. The Altay Kazakh was the most distantly related to Xishuangbanna Dai, while Altay Kazakh was the most closely related to Gansu Kazakh. The results may provide useful information for paternal lineages and increase our understanding of genetic relationships between two studied populations and other populations.